Cambridge Checkpoint Maths Workbook 2 - Wall, Terry (Hodder Education London, 2012)
This Workbook, for Cambridge Secondary 1 Maths, is fully matched to the Curriculum Framework, Cambridge Checkpoint Tests and the Cambridge Progression Tests.It offers your students essential practice to ensure a full understanding of topics. There is a parallel exercise for each exercise in the bestselling Student's Book, and students can write their answers in the Workbook, making them perfect for both classroom and homework use.